CTIM-09. PHASE I STUDY OF PD-L1 INHIBITION WITH AVELUMAB AND LASER INTERSTITIAL THERMAL THERAPY IN PATIENTS WITH RECURRENT GLIOBLASTOMA. (12th November 2021) - Hormigo, Adilia; Chiu, Daniel; Hahn, Mary; Qi, Jingjing; Lee, Brian; Mandeli, John; Ghatan, Saadi; Hadjipanayis, Constantinos; Yong, Raymund; Germano, Isabelle; Gnjatic, Sacha; Kim-Schulze, Seunghee
Abstract: BACKGROUND: The treatment of glioblastoma (GBM) poses many challenges. The use of immune checkpoint inhibition (ICI) has been disappointing as GBM is characterized by a low mutational burden and low infiltration by T cells. The combination of ICI with other treatment modalities may improve efficacy. METHODS: Patients with recurrent GBM were treated with 800 mg avelumab, a human IgG1 antibody directed against PD-L1, either alone (in part A) or within a week after MRI-guided laser interstitial thermal therapy (LITT, in part B) and by-weekly thereafter (NCT03341806). To spare steroid use, bevacizumab was allowed to be combined with avelumab. The primary objective was to characterize the tolerability and safety of the regimen. The secondary objectives included overall survival, progression-free survival, and signature of plasma analytes. RESULTS: A total of 12 patients (median age 64, range 37 - 73) enrolled from June 2018 to November 2019, 5 in part A and 7 in part B. Three serious adverse events (SAE) occurred in the same patient, not leading to death. There were 94 AEs reported, 5 grade 3, 28 grade 2, and 61 grade 1. The median PFS was 16.7 weeks (range 7.4-56.7) for patients in Part A and 30.9 weeks (range 8.5-77.7) for patients in Part B. The median survival for patients in part A was 11 months and 13.5 months for part B. The risk ratio of death by combining bevacizumab was 0.573 (p=0.258) with significantly decreased levels of peripheral blood plasma inflammatory markers such as EGF, CXCL5, VEGFA, LAP.TGβ1, ANGPT2 in women. CONCLUSIONS: Avelumab was generally well-tolerated, and the combination with LITT had a manageable safety profile and increased survival in a subset of patients. The addition of bevacizumab may increase survival by lowering cytokine expression in a gender-dependent manner. These results warrant further investigation in the next phase study.